Dreams, Sufism and Sainthood, The Visionary Career of Muhammad al-Zawâwî. - Katz (Numen Book Series, 1996)
Based on Muhammad al-Zawâwî's extraordinary diary of 109 dream conversations with the Prophet Muhammad, this study provides a rare, intimate view of 15th-century North African Muslim life. The study reconstructs Zawâwî's lifestory over a critical ten-year period and examines his career as a sufi in the historical context of North Africa and Mamluk Cairo. Psychological aspects of Zawâwî's religious experience are thoroughly explored. The concluding chapter provides an introduction to the role of dreams and visions in medieval Islam. Particular attention is paid to the way Zawâwî and his successors used their visions to legitimate claims to being awliya' , or living saints.